Geological and Geomorphological Studies in Parts of Angkola Sangkunur District, South Tapanuli Regency, North Sumatra - Azzaenuri, Mohammad Fachri; Rosana, Mega Fatimah; Sunarie, Cecep Yandri; Angga Syahputra, Muhammad Eko; Marbun, Ardiansyah (Journal of Geological Sciences and Applied Geology, 2023)
This research focuses on studying geological conditions that develop in the research area which is based on studies related to geomorphology, stratigraphy and geological structures that develop in the research area. In this research, the data used comes from mapping and taking surface data in a research area with an area of 12.5 km2, followed by petrographic analysis to determine the types of rocks found in the research area. The research area is divided into three geomorphological units, namely Sloping Volcanic-Structural Rolling Hills, Steep Volcanic-Structural Hills, and Sloping Volcanic-Structural Rolling Hills. The drainage pattern in the research area consists of parallel patterns in almost the entire area and sub-dendritic flow patterns in the central part of the area. The research area is composed of 3 lithologies, from old to young, namely, andesite, diorite which was formed as an intrusion, and breccia which consists of polymic and monomic breccia with fragments in the form of andesite, diorite, quartz fragments and carbon. The structures in the study area have the main directions northwest-southeast and northeast-southwest, both of which influence the morphology of the study area.